Enhancing senior high school students' visual imagery creativity in geometry through Geoboard - Hengki, Marius; Jamiah, Yulis; Yundari, Yundari (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study examines innovative learning tools to enhance students' understanding of geometry subjects. The research aims to describe the use of Geoboards in fostering the visual imagery creativity of 12th-grade students in geometry learning. The method used is descriptive qualitative, with subjects consisting of six students selected through purposive sampling. The results show that students with high visual imagery creativity possess good abilities in fluency, diversity, originality, and detail aspects. Students with moderate creativity still require guidance, while students with low creativity experience difficulties and need intensive practice. Using Geoboards has proven effective in enhancing visual imagery creativity, making learning more interesting and meaningful, and facilitating understanding of three-dimensional geometric concepts. The implications of this research suggest that Geoboards can be an effective learning tool in mathematics education.